Lunar neutron energy spectra from isotope abundance measurements on cadmium, samarium and gadolinium. - Sands, Daphne G. (Curtin University, 1998)
This thesis provides new evidence which contributes to a clearer understanding of the mixing history of the lunar soil, the interactions of cosmic rays with the lunar surface and any temporal and spatial variations in cosmic ray intensity at the lunar surface. The bombardment of the lunar surface by cosmic rays produces secondary neutrons which are thermalised by the lunar soil. These thermal neutrons are captured by trace elements with large neutron capture cross sections such as cadmium, gadolinium and samarium. Measurements by thermal ionisation mass spectrometry of the changes in the isotopic abundances of cadmium, gadolinium and samarium due to neutron capture are presented in this thesis. Evidence is also presented of the first observations of mass fractionation in cadmium in lunar soils.Changes have been observed in samples from the Apollo 14, 16 and 17 missions. In 114 [superscript 114]Cd/[superscript 113]Cd changes of 0.3% to 0.5% have been observed in lunar samples 60501,105, 65701,23 and 72161,73, of 0.4% and 0.8% in [superscript 158]Gd/[superscript 157]Gd in samples 14163,848 and 60501,105 and of 0.8%, 1.2% and 0.06% in [superscript 150]Sm/[superscript 149]Sm in samples 14163,848 and 60501,105 and 74220,125 respectively. This is the first time that neutron capture has been detected in cadmium. Mass fractionation effects of 0.30%, 0.53% and 0.54% per mass unit have been observed in lunar samples 60501,105, 65701,23 and 72161,73, the first cadmium mass fractionation observed in lunar soils. The cause of elemental mass fractionation on the Moon is not yet understood. These new data from cadmium, a volatile element with a large mass range from [superscript 106]Cd to [superscript 116]Cd is a valuable contribution to the debate.Thermal neutrons are captured preferentially at resonance energies of 0.03 eV by [superscript 155]Gd and [superscript 157]Gd, at 0.09 eV by [superscript 149]Sm and at 0.178 eV by [superscript 113]Cd. A comparison of the changes in [superscript 114]Cd/[superscript 113]Cd, [superscript 156]Gd/[superscript 155]Gd, [superscript 158]Gd/[superscript 157] and [superscript 15O]Sm/[superscript149]Sm due to neutron capture can therefore indicate the relative energies of the neutrons.Previous work has compared changes in [superscript 158]Gd/[superscript 157]Gd and [superscript 150]Sm/[superscript 149]Sm, this work extends the comparison with the new measurements of the changes in 114 [superscript 114]Cd/[superscript 113]Cd, This thesis shows that the intensity of the thermal neutrons peaks at a higher energy than the <0.1 eV assumed by Lingenfelter et al. (1972). The capture rate for gadolinium calculated by Lingenfelter, has been shown to be too high, this thesis shows that if a modified energy spectrum is considered, biased towards higher energies, it will bring the calculated neutron capture rate by gadolinium closer to the measured rates.The concentrations of cadmium, gadolinium and samarium in nine lunar samples have been measured for the first time by high precision isotope dilution mass spectrometry. Cadmium in 10017,341, 14310,615, 15041,188, 15059,240, 60501,105, 65701,23, 72161,73 and 74220,125 is 10.0_+0.2, 1.51_+0.02, 32.8+_0.6, 34.9+_0.3, 112+_2, 68.3_+0.8, 57.0+_0.6 and 300+_7 ppb respectively. Gadolinium concentrations of 21+_7 ppm in 14163,848, 3.26+_0.05 and 5.8_+0.3 ppm in 60501,105, and 8.1+_0.2 and 8.6+_0.1 ppm in 74220,125 are presented. Samarium concentrations of 24.3_+0.4 and 29.8_+0.5 ppm were found in 14163,848, 2.68+_0.04 and 14+2 ppm in 60501,105, and 6.3+_0.1 and 6.8+_0.1 ppm in 74220,125.The concentrations of cadmium, gadolinium and samarium in the seven geochemical reference materials BCR-1, BHVO-1, BIR-1, DNC1, MAG-1, PCC-1 and W-2 are also presented, some measured for the first time by isotope dilution mass spectrometry.